Modeling of the Refractive Index for the Systems Mx+H2o, M2x+H2o, H3bo3+Mx+H2o, and H3bo3+M2x+H2o. M = K+, Na+, or Li+ and X = Cl− or So42− - Soto-Gomez, J (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
The modeling of the refractive index for binary aqueous solutions of boric acid, sodium chloride, potassium chloride, sodium sulfate, lithium sulfate, and potassium sulfate, as well as ternary aqueous solutions of boric acid in the presence of sodium sulfate, lithium sulfate, or potassium chloride, is reported. The refraction index was represented by molar refraction. It was described as the sum of solutes’ partial molar refraction and solvent molar refraction. The solutes’ partial molar refraction was estimated from the molar refraction of the binary solutions. The excess molar refraction for these systems was described with the equation of Wang et al. The polarizability of the solutes present in the studied systems was estimated using the Lorenz– Lorenz relation. The results showed the model is appropriate for describing the systems studied; the interactions of boric acid, sodium, potassium, lithium, chloride, and sulfate ions with water molecules are relevant to explain the molar refraction and refractive index, and those for the binary systems of lithium chloride and sodium chloride are also relevant the ion–ion interactions. The model is robust and presents estimation capabilities within and beyond the concentrations and temperature range studied. Therefore, the outcomes represent valuable information to understand and follow the industrial processing of natural brines. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.